FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) - Herlina Susmaneli; Wenni Ardianti (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2018)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus is transmitted by the mosquito Aedes Aegypty. Pekanbaru city is one of the cities in the province of Riau which is endemic dengue hemorrhagic fever (DHF). Puskesmas Payung Sekaki is one of the puskesmas with incidence rate exceeding the limit endemisitas namely 64,7 per 100.000 population. The purpose of this research to know the relationship between knowledge, 3ms plus, habits nap, the existence of larva and hanging clothes with a dengue hemorrhagic fever. The kind of research used is analytic quantitative observational with the design case control. The sample it consists of 76 cases and 76 control. The data collection was done by interviews by using the questionnaire and observation. The sampling techniques used in this research is the Nonprobability Sampling is by Quota Sampling. The method of analysis data covering analysis univariat and analysis bivariat, use chi-square test. The results of the analysis bivariat show variable are associated with the occurrence of dengue hemorrhagic fever the knowledge (P= 0.0001) (OR=4,6 95% CI=2.299-9.205), 3ms plus (P=0.0018) (OR 2.4 95% CI=1.209-4.724), habits nap (P=0.003) (OR=2.9 95% CI=1.471-5.620, the existence of larva (P=0.0018) (OR=2.4 95% CI=1.209-4.724 and hang clothes (P=0.002 ) (OR=3.1 95% CI=1.547-6.307). It is recommended to the clinics is to increase public awareness about the prevention of dengue dengue hemorrhagic fever (DHF) as well as improved health program especially environment-based programs.